(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the role of the Maria Montessori method in the preschool education system, its didactic principles, and its effectiveness in forming children's cognitive processes. Furthermore, it provides specific facts and methodological recommendations for the practical implementation of the method.